Effectiveness of Labor Inspection to Protect Working Children Under Law No. 13 of 2003 on Labor in Bone County (International Journal of Scientific Research and Management (IJSRM), 2019)
This study aimed to analyze the effectiveness of labor inspection in the protection of child labor. The method used method by using a case study approachsocio-legal, The results showed that (1). Labor inspection effectiveness in preventing child labor in Bone regency showing the supervision has not been effective. This is because the quantity of labor inspectors is still lacking, it is not directly proportional to the number of companies and workers to be monitored, the lack of infrastructure and availability of funds. (2). Efforts to streamline the labor inspection to prevent child labor in Bone regencyThe main key is the commitment of all parties, especially the local government to make children as a priority in development. Real effort is to create specific regulations related to the ban on child labor, creating an environment that promotes the protection of children, turn on the values ​​and traditions that promote the dignity of the child, explore and mobilize resources to support the implementation of child protection. Other than that,strengthen labor inspection with inspectors establish reporting systems online. Keywords: Government, Commerce and Women